THE INFLUENCE OF THE NUMBERED HEAD TOGETHER (NHT) METHOD IN IMPROVING CLASS VIII STUDENT LEARNING OUTCOMES IN PAI SUBJECTS AT SMP NEGERI 2 BANDAR MASILAM SIMALUNGUN REGENCY - Chairuddin Siregar; Riza Apriyani (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
This type of research is quantitative research with an experimental method approach.The results of the research in this thesis, the learning model used in this study is Number Head Together (NHT). The obstacles encountered in implementing the Numbered Head Together (NHT) learning method are first, students are not familiar with the Numbered Head Together (NHT) learning method. Second, the relationship between students and friends in one discussion group in teaching and learning activities is still lacking. Third, the participation and seriousness of students in teaching and learning activities is still lacking. Fourth, the lack of effective use of time in teaching and learning activities. Fifth, there were some students who could not answer the questions. The solution to facing these obstacles is the need to use the Numbered Head Together (NHT) learning method in learning, not only in the subjects of Islamic Religious Education but in other subjects. In addition, it is necessary to reduce the use of the lecture method in the application of the Numbered Head Together (NHT) learning method, and a teacher needs to look at the abilities of each student, so that the distribution of groups is fair and equitable. The use of the Numbered Heads Together method affects student learning outcomes. It is known that there is a significant (real) difference between the average student learning outcomes in the experimental class and the control class. In addition, seen from the results of posttest calculations for the experimental class using the Numbered Heads Together method, the average value was 77.70. this shows a higher value compared to the control class that does not use the Numbered Heads Together method obtained 65.00. Thus the average value of student learning outcomes taught by the Numbered Heads Together method is significantly higher than the students taught not using the Numbered Heads Together method.